Comparing Behavioural Heterogeneity Across Asset Classes - Cars H. Hommes; Remco C.J. Zwinkels; Saskia ter Ellen (Norges Bank, 2017)
We estimate a generic agent-based model in which agents have heterogeneous beliefs about the future price to see to what extent behaviour differs across assets, and what this implies for market stability. We find evidence for behavioural heterogeneity for all asset classes, except for equities. Heterogeneity is especially pronounced for macro-economic variables. Agents update their beliefs frequently in financial markets, and only gradually in the case of macro-economic variables. Consequently, we find that the probability of behavioural bubbles is substantially higher for the macro-economic variables than for financial assets.
hdl:11250/2495572
Keywords: E31; G12; G15; 330; financial markets; heterogeneous expectations; market stability